Dampak Psikologis Pembelajaran Daring di Sekolah Dasar - Subur Subur; Irra Wahidiyati (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2022)
This case study research aims to explore the psychological impact of online learning on teachers, students, and parents through observation and interviews with teachers, students and parents in elementary schools. The findings of the study reveal that online learning impacted teachers because they worked beyond the allotted time, they could not recognize students well, they had difficulty in monitoring students’ learning processes, and they found it difficult to determine student learning outcomes. The students’ discipline level lessened because the school hours are different from before the pandemic and their learning motivation decreased. As for the parents, online learning added to the burden in terms of costs, time and thoughts.Keywords: Online learning; pandemic period; psychological impact